Analisis Fatigue Life Konstruksi Utama Slopeway KM. Dharma Rucitra VIII - Kinanti Armelya Kurniati; Pranowo Sidi; Hariyanto Soeroso (Proceedings Conference On Design Manufacture Engineering And Its Application, 2022)
One of the shipbuilding companies is repairing Cargo Ro-Ro Ships to become Passenger Ro-Ro Ships. On this ship, it is planned that there will be additional decks that function as accommodation space and motorcycle parking. On the new deck there will be slopeway plan as an access to up and down motorbikes. This analysis was conducted to determine the fatigue life of the slopeway. FEM and simplified fatigue damage methods are used to calculate the safety of ship construction and estimate the age of a construction so as to minimize unpredictable damage. Analysis of this method using ANSYS software. Based on the results of the analysis that has been done, the value of the fatigue life in the construction of slopeway design 1 is 28 years, the construction slopeway design 2 is 203 years and the construction slopeway design 3 is 107 years. In further research, it can be redesigned the slopeway construction so that the slopeway can accept a larger load and meet the IRClass standard. In addition, other methods and software can be used as a comparison in the fatigue life analysis.